Effect of different culture media, temperature and pH on growth and sporulation of Alternaria carthami: EFFECT OF CULTURE MEDIA, TEMPERATURE AND pH ON ALTERNARIA CARTHAMI - V M GHOLVE; S B GHUGE; S V PAWAR (Journal of Oilseeds Research, 2017)
Among the eight culture media tested for the growth of Alternaria carthami, the potato dextrose agar showed highest growth (90.00 mm) followed by potato malt agar (84.16 mm) and yeast mannitol agar (73.33 mm). The colony growth recorded in different temperature ranged from 5.66 mm at 5°C to 85.66 mm at 30°C. The highest mycelial growth (85.66 mm) was recorded at 30°C with excellent sporulation followed by 25°C (83.83 mm) and 20°C (66.33 mm). The colony growth recorded with all the pH levels was ranged from 30.50 mm at pH 4.0 to 85.83 mm at pH 6.5, the maximum mycelial growth (85.83 mm) was recorded at pH 6.5 with excellent sporulation, followed by pH 6 (82.00 mm) and pH 7 (70.33 mm) with excellent and good sporulation, respectively.